Análisis del sistema informático para el control académico en el Instituto Proezas en la ciudad de Babahoyo. - Del Barco Cedeño, Ronny Daniel (2023)
This investigative work was carried out with the objective of analyzing the computer system for academic control at the Instituto Proezas in the City of Babahoyo, this topic arises due to the importance of computer systems that have become an integral part of academic control, the The use of technology has revolutionized the way in which academic institutions manage and control their operations, the problem of this study affects the Institution is mainly the secretary who performs the following processes manually and some documents are done in Word and Excel this leads to running the risk of losing information the methodology used in this work is of a descriptive research type to describe a phenomenon or group of phenomena through observation and measurement, the research design is mixed this wants say that both the qualitative and quantitative methods were used since surveys were carried out on the population The relation of this work is 107 students giving a sample of 84 people to be surveyed, later statistical analysis was carried out and also an interview with the secretary of this institute, in order to know their academic processes within the academic center. The line of research that is related to the information and communication system, entrepreneurship and innovation in conjunction with the subline of networks and intelligent software and hardware technologies.